God vs. Government : taking a biblical stand when Christ & compliance collide - Busenitz, Nathan; Coates, James (Eugene, Oregon : Harvest House Publishers, 2022)
"How can we as Christians know how best to respond when the state encroaches upon the church? God vs. Government looks to the Bible for answers about remaining discerning and faithful to our heavenly Father's commands even when society tells us to do otherwise"--
Includes bibliographical references (pages 203-206).
Keywords: COVID-19 (Disease) -- Religious aspects -- Christianity; COVID-19 Pandemic, -- 2020- -- Religious aspects Christianity -- Canada; Church and state; Church and state -- Canada -- History -- 21st century